The Effect of Eye-stalk and Anti-dopamine on Number of Eggs and Nauplii Production in Vannamei Shrimp (Litopenaeus vanammei) - Jovita Larasati Poetri Tajuw; Pande Gde Sasmita Julyantoro; Gde Raka Angga Kartika (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
One of the shrimp commodities in high demand on the global market is the vannamei shrimp (Litopenaeus vannamei), and Indonesia is one of the leading countries in shrimp production. To improve the growth and quality of vannamei shrimp production, farming techniques continue to be developed. The practice of eye-stalk cutting on shrimp, also known as eyestalk-cutting, has become a technique actively employed in shrimp farming. However, it is considered a violation of animal welfare regulations. Anti-dopamine is another alternative that can inhibit the gonad maturation inhibiting hormone and improve shrimp reproductive performance. This study aims to determine the effect of eye stalk and anti-dopamine injection on the comparison of egg and nauplii production as well as the hatching rate carried out at Balai Produksi Induk Udang Unggul dan Kekerangan (BPIU2K) in Karangasem, Bali. The research method employed was experimental, with data analysis conducted using an independent t-test. The results showed that eye-stalk produces ±269,000 eggs with a hatching rate (HR) of 26.13%, while anti-dopamine can produce up to ±91,600 eggs with an HR of 83.31%. Total nauplii production from eye-stalk treatment reached ±75,000, and anti-dopamine nauplii production reached ±77,100. T-test results with a 95% significance level indicate a difference in the number of eggs but no significant difference in total nauplii production